KEDUDUKAN DAN STATUS ANAK YANG DILAHIRKAN SECARA BAYI TABUNG DILUAR PERKAWINAN DALAM PERSPEKTIF HUKUM PERDATA - Muhammad Auliya Putra (Universitas 17 Agustus 1945 Samarinda, 2021)
ABSTRACTEvery human being who wants offspring must go through the marriage process but there are solutions for those who want offspring but not necessarily through marriage, such as phobias and there are also those who have problems such as not wanting to get married but are told to get offspring and have problems getting married. These problems will cause many complications related to how the child's survival is especially in terms of the law that regulates the child being born because of problems outside of marriage or not a legal marriage. The legal basis relating to children born by IVF outside of marriage is Article 272 of the Civil Code and the Decision of the Constitutional Court (MK) Number 46 / PUU-VIII / 2010 which revised Article 43 paragraph (1) of the Marriage Law. The formulas of the problem are: (1) The position and status of children born by IVF outside of marriage in the perspective of Civil Law; (2) The legality of children born in IVF outside of marriage in the perspective of Civil Law.The type of research used in this research is Normative Juridical Research and the problem approach used in this study is the Statute Approach and the Conceptual Approach.The results of the research are with the existence of Article 272 of the Civil Code which states that the validity of the child can be recognized as long as it receives legal recognition from the father and mother and also through the marriage certificate itself and the Constitutional Court (MK) Decision Number 46 / PUU-VIII / 2010 which revises Article 43 Paragraph (1) of the Marriage Law which states that the civil relationship of children born outside of marriage has a relationship only with the mother and the mother's family, as well as with the man as the father, which can be proven based on science and technology to have a blood relationship with the father's family. This Constitutional Court Decision Number 46 / PUU-VIII / 2010 provides legal protection for children to provide fair certainty for the status of children born even though the legality of the marriage is still not legal according to State law. So that the blood relationship between the child and the father in a biological sense can be confirmed based on a legal process and is able to receive their rights as a legitimate child. My advice is that it would be nice if you get married first so that babies born from IVF programs outside of marriage get guaranteed legal certainty and it is better for parents who give birth to children outside of marriage to acknowledge or legalize the child so that the child can get family status as soon as possible.Keywords: The Position and Status, Children, In Vitro Fertilization, Outside Marriage, Civil Law.